Sepsis Upregulates CD14 Expression in a MyD88-Dependent and Trif-Independent Pathway. Issue 1 (January 2018) - Chen, Zhixia; Shao, Zhenzhen; Mei, Shuya; Yan, Zhengzheng; Ding, Xibing; Billiar, Timothy; Li, Quan
Abstract : ABSTRACT: An overwhelming immune response, particularly from macrophages, plays a critical role in survival and organ damage in sepsis patients. Toll-like receptors (TLRs) are important receptors to recognize the conserved motifs expressed by invading bacteria. The TLRs except TLR3 signal via a MyD88-dependent pathway. TLR3 uses a TRIF-dependent pathway, while TLR4 uses both MyD88 and TRIF-dependent pathways. Previous studies indicated that CD14 was necessary for TLRs-dependent production of pro-inflammatory cytokines. Blocking CD14 protected against the deleterious systemic inflammatory response associated with sepsis. The aim of this study was to determine the signaling pathway of TLR activation-induced CD14 expression in models of polymicrobial sepsis and in peritoneal macrophages. We found that CD14 expression was upregulated in the lung, liver, and kidney of septic mice induced by cecal ligation puncture. In cultured peritoneal macrophages, specific agonists for all TLRs, except for TLR3, increased CD14 expression. Lipopolysaccharide-induced upregulation of CD14 was abolished in peritoneal macrophages from MyD88 KO mice but increased in TRIF inhibitor, resveratrol pretreated wild-type macrophages. Moreover, MyD88 KO, but not TRIF KO mice, showed a decreased CD14 expression in the tissue of septic mice, which was associated with a strongly attenuated inflammatory response and increased survival rate. These data suggest that a MyD88-dependent and TRIF-independent pathway of TLR is activated in upregulating CD14 expression under septic conditions. This study deciphers a critical cross-talk between TLRs and CD14.